Reproductive benefits associated with dispersal in headwater populations of Trinidadian guppies (Poecilia reticulata). (25th November 2021) - Borges, Isabela L.; Dangerfield, Jillian C.; Angeloni, Lisa M.; Funk, W. Chris; Fitzpatrick, Sarah W.
Abstract: Theory suggests that the evolution of dispersal is balanced by its fitness costs and benefits, yet empirical evidence is sparse due to the difficulties of measuring dispersal and fitness in natural populations. Here, we use spatially explicit data from a multi‐generational capture–mark–recapture study of two populations of Trinidadian guppies ( Poecilia reticulata ) along with pedigrees to test whether there are fitness benefits correlated with dispersal. Combining these ecological and molecular data sets allows us to directly measure the relationship between movement and reproduction. Individual dispersal was measured as the total distance moved by a fish during its lifetime. We analysed the effects of dispersal propensity and distance on a variety of reproductive metrics. We found that number of mates and number of offspring were positively correlated to dispersal, especially for males. Our results also reveal individual and environmental variation in dispersal, with sex, size, season, and stream acting as determining factors. Abstract : We make use of a long–term mark–recapture study and multigenerational pedigrees of two wild populations of Trinidadian guppies ( Poecilia reticulata ) to explore the relationship between dispersal and fitness and how it varies across individuals and environments. We show that dispersal propensity and distance varies with sex, body size, stream, and seasonality. We also documented a striking and consistent reproductive benefit of dispersal for male guppies, wherein dispersing males had 35% more offspring than philopatric males when holding all other variables constant, and were 1.6 times as likely to have any offspring at all. Our results demonstrate that dispersal is a major determinant of male reproduction in Trinidadian guppies, and suggest that selection for increased reproductive output drives male–biased dispersal in this system.